SCHOOL LEADERSHIP EMPOWERMENT FOR IMPLEMENTING MERDEKA BELAJAR THROUGH PASSION-BASED LEARNING AT LABORATORY ELEMENTARY SCHOOL - Maisyaroh Maisyaroh; Sri Untari; Tutut Chusniyah; Desi Eri Kusumaningrum; Maulana Amirul Adha; Indra Lesmana; Hanika Angelie; Isadatul Fadhila (Faculty of Economics and Business, Universitas Negeri Jakarta, 2026)
This community service initiative sought to enhance school leadership and bolster teacher proficiency in executing the Merdeka Belajar (Freedom to Learn) curriculum via Passion-Based Learning at the Laboratory Elementary School of Universitas Negeri Malang, Blitar. The activity utilized a participative methodology comprising many phases: socialization, training, classroom implementation, mentoring, and assessment. Twenty participants, comprising one principal and nineteen instructors, engaged in the program. Quantitative data were gathered using pre-test and post-test instruments and analyzed using descriptive statistics and the Wilcoxon test, whereas qualitative insights were derived from reflection sessions and observations. The results indicated a substantial enhancement in participants' comprehension and abilities, with the average score rising from 68.81 (good) to 90.36 (very good). Participants exhibited enhanced confidence, teamwork, and motivation in implementing Passion-Based Learning within the Merdeka Belajar framework. The program effectively improved instructional leadership, cultivated a passion-driven school culture, and established a sustainable framework for executing meaningful, student-centered learning.